A carbonyl sulfide hydrolysis catalyst and preparation method thereof
By using block copolymers, dopamine hydrochloride and paraformaldehyde and combining mechanical grinding, high temperature carbonization and potassium hydroxide etching treatment, a nitrogen-doped porous carbon catalyst with high catalytic activity and strong nitrogen doping ability was prepared. The problems of cumbersome catalyst preparation process and poor catalytic activity in the prior art have been solved.
Patent Information
- Application Number
- CN202111151675.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-09-29
AI Technical Summary
The preparation process of existing nitrogen-doped porous carbon catalysts is cumbersome and difficult to operate. The catalyst has low nitrogen doping ability and poor catalytic activity, making it difficult to effectively remove carbonyl sulfur.
Using block copolymer, dopamine hydrochloride and paraformaldehyde as raw materials, nitrogen-doped porous carbon catalysts with ordered mesoporous structures and rich structural defects were prepared through mechanical grinding, high-temperature carbonization and potassium hydroxide etching treatment.
The prepared catalyst has strong nitrogen doping ability and high catalytic activity, and can achieve 100% hydrolysis conversion rate at 70°C. The preparation method is simple to operate and easy to control.
Smart Images

Figure CN115869978B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbonyl sulfide hydrolysis catalyst preparation, and in particular to a carbonyl sulfide hydrolysis catalyst and a preparation method thereof. Background Art
[0002] In the actual natural gas extraction process, the gaseous mixture obtained from different geological extraction often contains a certain concentration of gaseous sulfides, which can be mainly divided into inorganic sulfides (H2S) and organic sulfides (COS, CS2, etc.) according to their composition. These gaseous sulfides are extremely toxic. They not only corrode pipeline equipment in the chemical production process, but also poison industrial catalysts and lose their activity; and their large-scale emissions will threaten human health and cause damage to the environment. Based on these hazards, sulfur-containing gases must be treated before they are used in subsequent processes or discharged into the atmosphere.
[0003] At present, common commercial metal catalysts, such as Fe3O4, show weak catalytic activity and short service life when used for catalytic elimination of carbonyl sulfide because sulfides can deactivate metal active sites or long-term exposure to water vapor environment causes leaching of supported base active sites. Therefore, metal-free catalysts with structural base sites (such as nitrogen) have been widely studied. It is found that compared with supported metal base sites, metal-free structural base nitrogen sites are anchored to the network of the support through covalent bonds, which shows excellent sulfur resistance and good stability in the reaction. As a new class of materials, nitrogen-doped ordered mesoporous carbon has a variety of structural base nitrogen sites and shows important application potential in catalytic elimination of carbonyl sulfide. However, the current preparation process of nitrogen-doped porous carbon catalysts has the disadvantages of cumbersome process, difficult operation, low nitrogen doping ability of catalyst products, and poor catalytic activity. Summary of the invention
[0004] The purpose of the present invention is to provide a carbonyl sulfide hydrolysis catalyst and a preparation method thereof. The preparation method provided by the present invention is simple to operate and easy to control. The prepared catalyst has an ordered mesoporous structure and abundant structural defects, more nitrogen sites, stronger nitrogen doping ability, and exhibits higher catalytic activity when catalyzing the elimination of carbonyl sulfide.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] A method for preparing a carbonyl sulfide hydrolysis catalyst comprises the following steps:
[0007] Step 1, weighing the block copolymer, dopamine hydrochloride and paraformaldehyde, mixing and grinding them evenly to obtain a first material;
[0008] Step 2, subjecting the first material obtained in step 1 to high-temperature carbonization treatment under nitrogen conditions to obtain a second material;
[0009] Step 3, mixing the second material obtained in step 2 with potassium hydroxide powder and grinding them, and then etching the ground material under nitrogen conditions to obtain a third material; wherein the weight ratio of the potassium hydroxide powder to the second material is 0.5 to 1.5:1;
[0010] Step 4, neutralizing the third material obtained in step 3 with an acid solution, washing to neutrality, and drying to obtain a carbonyl sulfide hydrolysis catalyst;
[0011] Wherein, in the step 1, the raw materials are added in amounts by weight: 15 to 25 parts of the block copolymer; 3 to 6 parts of dopamine hydrochloride; and 4 to 8 parts of paraformaldehyde.
[0012] The invention discloses a method for preparing a carbonyl sulfide hydrolysis catalyst. In the preparation process, a block copolymer, dopamine hydrochloride and paraformaldehyde are used as raw materials, and high-temperature carbonization treatment is directly performed after uniform grinding. Then, the calcined product obtained after carbonization is mixed with potassium hydroxide powder for rapid grinding, and then etching carbonization treatment is performed under nitrogen protection, washing, and drying to obtain the carbonyl sulfide hydrolysis catalyst. The method uses three raw materials to mechanically grind to achieve a simple, green and rapid synthesis of nitrogen-doped mesoporous polymers. After high-temperature carbonization, an amorphous carbon skeleton can be formed. After high-temperature activation treatment with potassium hydroxide, rich structural defects are formed. The rapid activation of KOH is a key step to improve the porosity and nitrogen doping of the sample. The nitrogen-doped porous carbon prepared in this way forms a variety of structural base nitrogen sites.
[0013] This method uses a solvent-free method to prepare a new type of nitrogen-doped porous carbon catalyst. Through the coordinated cooperation of three processes including mechanical grinding, high-temperature calcination and KOH etching treatment, as well as targeted adjustment of influencing factors such as raw material ratio and process parameters, the prepared carbonyl sulfide hydrolysis catalyst has an ordered mesoporous structure and rich structural defects, more nitrogen sites, and stronger nitrogen doping ability. It exhibits higher catalytic activity when catalyzing the elimination of carbonyl sulfide. In addition, the preparation method is simple to operate and easy to control.
[0014] Furthermore, in the step 1, the weight ratio of the dopamine hydrochloride to the paraformaldehyde is 0.5 to 2:1. Studies have found that the mass ratio of the raw material dopamine hydrochloride to paraformaldehyde is an important factor affecting the catalytic activity of the carbonyl sulfide hydrolysis catalyst. When the mass ratio of dopamine hydrochloride to paraformaldehyde is too small or too high, the catalytic activity of the prepared catalyst will show a significant downward trend. The framework and structural defects of the porous carbon in the entire catalyst preparation process have a direct impact on the manifestation of nitrogen doping ability. Preferably, in the step 1, the weight ratio of the dopamine hydrochloride to the paraformaldehyde is 0.5 to 1:1. The prepared carbonyl sulfide hydrolysis catalyst has a high catalytic activity.
[0015] Furthermore, the molecular formula of dopamine hydrochloride is C8H 11 NO2·HCl, white needle-shaped crystals or crystalline powder, also known as 4-(2-aminoethyl)-1,2-benzenediol hydrochloride.
[0016] Furthermore, the polyformaldehyde CAS number: 30525-89-4; molecular formula: HO-(CH2O)nH, n=10-100; molecular weight: (30)n; properties: white combustible crystalline powder with formaldehyde odor; density (g / mL, 20°C): 1.45; relative vapor density (g / mL, air=1): 1.03; melting point (°C): 163-165.
[0017] Furthermore, in step 1, the block copolymer is F127 or P123. P123 and F127 are both triblock polymers, and they are both a type of polyether. EO-PO type polyether Pluronic F127 and P123 are called: polyoxyethylene-polyoxypropylene-polyoxyethylene, and their molecular formula is: PEO-PPO-PEO.
[0018] Furthermore, in step 2, the high temperature carbonization treatment is carried out under the conditions of heating to 700-900° C. at a heating rate of 5-10° C. / min and maintaining the temperature for 30-90 min.
[0019] Furthermore, in step 3, the weight ratio of the potassium hydroxide powder to the second material is 1.0 to 1.5: 1. Studies have shown that the addition ratio of potassium hydroxide powder is a very important key factor affecting the performance of the catalyst product. Too small or too large an addition ratio will affect the porosity and nitrogen doping effect of the catalyst sample, and will also greatly reduce the catalytic activity of the carbonyl sulfide hydrolysis catalyst.
[0020] Furthermore, in step 3, the etching treatment condition is to heat to 800-900°C at a heating rate of 1-2°C / min and maintain for 60-120min. Studies have found that the temperature of the etching treatment is a very important key factor affecting the performance of the catalyst product. If the etching treatment temperature is too low or too high, it will affect the porosity and nitrogen doping effect of the catalyst sample, and will also greatly reduce the catalytic activity of the carbonyl sulfide hydrolysis catalyst.
[0021] Furthermore, in step 4, the acid solution is a sulfuric acid solution or a hydrochloric acid solution with a concentration of 0.2 to 2 mol / L.
[0022] Furthermore, in step 4, the drying temperature is 60-120° C., and the drying time is 12 h to 28 h.
[0023] Another object of the present invention is to provide a product prepared by the method for preparing the carbonyl sulfide hydrolysis catalyst.
[0024] A carbonyl sulfide hydrolysis catalyst prepared by the method for preparing the carbonyl sulfide hydrolysis catalyst.
[0025] The catalyst prepared by the invention has an ordered mesoporous structure and abundant structural defects, more nitrogen sites, stronger nitrogen doping ability, and exhibits higher catalytic activity when catalyzing the elimination of carbonyl sulfide.
[0026] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0027] The invention discloses a method for preparing a carbonyl sulfide hydrolysis catalyst. In the preparation process, block copolymer, dopamine hydrochloride and paraformaldehyde are used as raw materials, and high-temperature carbonization treatment is directly performed after uniform grinding. Then, the calcined product obtained after carbonization is mixed with potassium hydroxide powder for rapid grinding, and then etching carbonization treatment is performed under nitrogen protection, washing, and drying to obtain the carbonyl sulfide hydrolysis catalyst. The method adopts a solvent-free method to prepare a new type of nitrogen-doped porous carbon catalyst. Through the coordinated cooperation of three processes of mechanical grinding, high-temperature calcination and KOH etching treatment, and targeted adjustment of influencing factors such as raw material ratio and process parameters, the prepared carbonyl sulfide hydrolysis catalyst has an ordered mesoporous structure and rich structural defects, more nitrogen sites, and stronger nitrogen doping ability. It shows high catalytic activity when catalytically eliminating carbonyl sulfide. At 70°C, the COS hydrolysis catalytic conversion rate can reach 100%, and the preparation method is simple to operate and easy to control. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the XRD pattern of the carbonyl sulfide hydrolysis catalyst prepared in Example 1.
[0029] Figure 2This is the Raman image of the carbonyl sulfide hydrolysis catalyst prepared in Example 1. DETAILED DESCRIPTION
[0030] The present invention will be described in detail below in conjunction with the accompanying drawings.
[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] Example 1
[0033] The preparation of carbonyl sulfide hydrolysis catalyst comprises the following steps:
[0034] Step 1, weigh 2 g of block copolymer F127, 0.45 g of dopamine hydrochloride and 0.8 g of paraformaldehyde, mix them, and grind them in a mortar for 5 minutes until they are evenly ground to obtain a first material;
[0035] Step 2, the first material obtained in step 1 is loaded into a ceramic firing boat, and then the firing boat is transferred to a tube furnace, heated to 900° C. at a heating rate of 8° C. / min under nitrogen conditions, maintained for 70 min, and subjected to high-temperature carbonization treatment to obtain a second material;
[0036] Step 3, mixing potassium hydroxide powder and the second material obtained in step 2 at a mass ratio of 1.2:1, and then quickly grinding them, and then transferring the ground materials to a tube furnace and heating them to 900° C. at 1.5° C. / min under nitrogen conditions, maintaining them for 80 minutes, and performing etching treatment to obtain a third material;
[0037] Step 4: neutralize the third material obtained in step 3 with 0.7 mol / L hydrochloric acid for 12 hours, wash with water until neutral, and then dry at 110° C. for 15 hours to obtain a carbonyl sulfide hydrolysis catalyst.
[0038] XRD and Raman tests were performed on the carbonyl sulfide hydrolysis catalyst prepared in Example 1. The test results are as follows: Figure 1 and 2 shown. Figure 1 The XRD pattern of nitrogen-doped carbon is shown. The sample has two relatively weak diffraction peaks at 23.3° and 43.5°, corresponding to the (002) and (100) crystal plane diffraction of the carbon material, respectively, indicating that the synthesized nitrogen-doped carbon sample has a typical amorphous carbon skeleton and abundant structural defects. Among them, the formation of the amorphous carbon skeleton is related to the carbonization temperature, and a large number of structural defects come from the high-temperature activation of KOH. Figure 2 The Raman spectra of nitrogen-doped carbon are shown. The Raman spectra of the sample are at 1350 and 1595 cm -1There are two obvious characteristic peaks near 1350cm, which are respectively attributed to the D-band and G-band absorption peaks of the graphite phase in the carbon material structure. -1 The D-band absorption peak near 1595 cm indicates that there are abundant defects inside the material. -1 The G band absorption peak near the nitrogen-doped carbon material indicates that there is a graphite carbon SP in the two-dimensional hexagonal lattice. 2 Further calculation of the relative intensity of the D-band and G-band peaks (I G / I D ) found that its G / I D It is about 1.75 to 2.12, indicating that there are typical amorphous carbon networks and abundant structural defects in the nitrogen-doped carbon materials, which is consistent with the results of XRD analysis.
[0039] Example 2
[0040] The preparation of carbonyl sulfide hydrolysis catalyst comprises the following steps:
[0041] Step 1, weighing 1.5 g of block copolymer P123, 0.3 g of dopamine hydrochloride and 0.4 g of paraformaldehyde, mixing, grinding in a mortar for 5 min, grinding evenly, to obtain a first material;
[0042] Step 2, the first material obtained in step 1 is loaded into a ceramic firing boat, and then the firing boat is transferred to a tube furnace, heated to 700° C. at a heating rate of 5° C. / min under nitrogen conditions, maintained for 90 min, and subjected to high-temperature carbonization treatment to obtain a second material;
[0043] Step 3, mixing potassium hydroxide powder and the second material obtained in step 2 at a mass ratio of 1.5:1 and then quickly grinding them, then transferring the ground materials to a tube furnace and heating them to 800° C. at 1° C. / min under nitrogen conditions, maintaining them for 60 min, and performing etching treatment to obtain a third material;
[0044] Step 4: neutralize the third material obtained in step 3 with 0.2 mol / L sulfuric acid solution for 24 hours, wash with water until neutral, and then dry at 60° C. for 48 hours to obtain a carbonyl sulfide hydrolysis catalyst.
[0045] Example 3
[0046] The preparation of carbonyl sulfide hydrolysis catalyst comprises the following steps:
[0047] Step 1, weigh 2.5 g of block copolymer P123, 0.6 g of dopamine hydrochloride and 0.3 g of paraformaldehyde, mix them, and grind them in a mortar for 5 minutes until they are evenly ground to obtain a first material;
[0048] Step 2, the first material obtained in step 1 is loaded into a ceramic firing boat, and then the firing boat is transferred to a tube furnace, heated to 900° C. at a heating rate of 10° C. / min under nitrogen conditions, maintained for 30 min, and subjected to high-temperature carbonization treatment to obtain a second material;
[0049] Step 3, mixing potassium hydroxide powder and the second material obtained in step 2 at a mass ratio of 1:1 and then quickly grinding them, then transferring the ground materials to a tube furnace and heating them to 900° C. at 2° C. / min under nitrogen conditions, maintaining them for 60 minutes, and performing etching treatment to obtain a third material;
[0050] Step 4: neutralize the third material obtained in step 3 with 2 mol / L hydrochloric acid, wash with water until neutral, and then dry at 120° C. for 12 h to obtain a carbonyl sulfide hydrolysis catalyst.
[0051] Example 4
[0052] The preparation of carbonyl sulfide hydrolysis catalyst comprises the following steps:
[0053] Step 1, weigh 2 g of block copolymer F127, 0.5 g of dopamine hydrochloride and 0.5 g of paraformaldehyde, mix them, and grind them in a mortar for 5 minutes until they are evenly ground to obtain a first material;
[0054] Step 2, the first material obtained in step 1 is loaded into a ceramic firing boat, and then the firing boat is transferred to a tube furnace, heated to 800° C. at a heating rate of 6° C. / min under nitrogen conditions, maintained for 80 min, and subjected to high-temperature carbonization treatment to obtain a second material;
[0055] Step 3, mixing potassium hydroxide powder and the second material obtained in step 2 at a mass ratio of 0.5:1, and then quickly grinding them, and then transferring the ground materials to a tube furnace and heating them to 850° C. at 1.2° C. / min under nitrogen conditions, maintaining them for 100 minutes, and performing etching treatment to obtain a third material;
[0056] Step 4: neutralize the third material obtained in step 3 with 1.5 mol / L hydrochloric acid, wash with water until neutral, and then dry at 105° C. for 24 hours to obtain a carbonyl sulfide hydrolysis catalyst.
[0057] Test 1:
[0058] The carbonyl sulfide hydrolysis catalyst prepared in Examples 1-4 was evaluated for activity in a COS hydrolysis evaluation device, which has the following steps: 3 ml of each catalyst sample prepared in Examples 1-4 was taken, and the sample was placed at the bottom of a thick tube of a U-shaped sample tube filled with quartz wool during measurement, and the sample tube was placed in a heating furnace and the pipeline was connected. N2 and COS were used as raw gas, and water vapor was introduced for carbonyl sulfide hydrolysis catalysis. The raw gas flow rate was 20 mL / min, the test reaction temperature was 30-170°C, and the heating rate was 3°C / min. The COS content at the inlet and outlet of the device was determined by gas chromatography, and the activity of the above carbonyl sulfide hydrolysis catalyst sample was characterized by calculating the conversion rate of COS under the condition of 30°C-170°C.
[0059] The test found that the catalytic activity of the carbonyl sulfide hydrolysis catalysts prepared in Examples 1-4 was very low at 30°C, all at about 10% in terms of COS conversion rate. As the temperature increased, the COS conversion rate continued to increase. At 50°C, the COS conversion rate of the catalyst in Example 1 reached 85.6%; the COS conversion rate of the catalyst in Example 2 reached 83.2%; the COS conversion rate of the catalyst in Example 3 reached 77.8%; and the COS conversion rate of the catalyst in Example 4 reached 81.5%.
[0060] Among them, the COS conversion rate of the catalyst prepared in Example 1 reached 100% at 70°C, and as the temperature increased, the COS conversion rate remained 100%. The COS conversion rate of the catalyst prepared in Example 2 reached 100% at 73°C. The COS conversion rate of the catalyst prepared in Example 3 reached 100% at 80°C. The COS conversion rate of the catalyst prepared in Example 4 reached 100% at 76°C. It can be seen from this that the carbonyl sulfide hydrolysis catalyst prepared in the present invention has an ordered mesoporous structure and abundant structural defects, more nitrogen sites, stronger nitrogen doping ability, and exhibits higher catalytic activity when catalyzing the elimination of carbonyl sulfide.
[0061] Comparative Example 1
[0062] Comparative Example 1: A second material was prepared according to the same preparation method as in Example 1, and the second material was subjected to the same method as in Test 1, with the second material being used as a catalyst for hydrolysis of carbonyl sulfide. The test results were as follows: as the temperature increased, the COS conversion rate remained essentially unchanged, and the conversion rate was relatively low, being only about 10%.
[0063] Comparative Example 2
[0064] The catalyst prepared in Comparative Example 2 was tested for hydrolysis catalytic activity using the same method as Test 1. The test results are as follows: As the temperature increases, the COS conversion rate remains essentially unchanged, and the conversion rate is relatively low, only about 30%.
[0065] In Comparative Example 2, the raw material mixture is directly etched, and the carbon material that has not been subjected to high-temperature carbonization treatment does not form an amorphous carbon skeleton, which directly leads to a significant reduction in the catalytic activity of the prepared catalyst.
[0066] Comparative Example 3
[0067] Comparative Example 3 provides a conventional carbonyl sulfide hydrolysis catalyst, which uses ethylenediamine as an alkaline modifier and commercially available activated carbon as a matrix, comprising the following steps:
[0068] Take 20g of anhydrous ethanol and a certain amount of ethylenediamine alkaline modifier, pour them into a beaker and let them stand for 30 minutes; then put the above solution into a three-necked flask, weigh 5g of activated carbon after alkali washing, and pour it into the three-necked flask.
[0069] The three-necked flask was placed in a constant temperature water bath, sealed and stirred at 80°C for 24 hours. After the reaction was completed, it was dried at 120°C for later use to obtain a catalyst.
[0070] The catalyst prepared in Comparative Example 3 was tested for hydrolysis catalytic activity using the same method as Test 1. The test results are as follows: As the temperature increases, the COS conversion rate increases slowly. When the temperature reaches 140° C., the COS conversion rate basically reaches 100%.
[0071] Comparative Example 4
[0072] Comparative Example 4 provides a common carbonyl sulfide hydrolysis catalyst, a method for preparing a regular mesoporous phenolic resin using ethanol and water as solvents and F127 as a block template, comprising the following steps:
[0073] (1) 0.9 g of F127 was added to 10 g of ethanol and 9 g of water and stirred to dissolve, followed by adding 1.25 g of phloroglucinol and stirring at room temperature for half an hour to achieve self-assembly between the template and phloroglucinol.
[0074] (2) Add 2.0 g of formaldehyde solution to the above system, stir at room temperature for 1 hour, and then open the lid to evaporate the solvent at room temperature for about 24 hours.
[0075] (3) The solid in the above reaction system is thermally cured at 150° C. for 24 hours to obtain a primary product of a mesoporous phenolic resin.
[0076] (4) The above-mentioned primary product is dispersed in a mixed solution of 50 ml of ethanol and 7 ml of concentrated hydrochloric acid, and refluxed at 90° C. for 24 hours to obtain a mesoporous phenolic resin material with open pores, thereby obtaining a catalyst.
[0077] The catalyst prepared in Comparative Example 4 was tested for hydrolysis catalytic activity using the same method as Test 1. The test results are as follows: As the temperature increases, the COS conversion rate increases slowly. When the temperature reaches 155°C, the COS conversion rate basically reaches 100%.
[0078] Studies have shown that, compared with the catalytic activity of conventional carbonyl sulfide hydrolysis catalysts in the prior art, the catalytic activity of the catalyst prepared in the present invention is effectively improved.
[0079] Examples 5-7 and Comparative Examples 5-6
[0080] Examples 5-7 and Comparative Examples 5-6 adopt the same preparation method as Example 1 to prepare carbonyl sulfide hydrolysis catalysts, except that the weight ratio of dopamine hydrochloride to paraformaldehyde is changed in Examples 5-7 and Comparative Examples 5-6, but the total amount of dopamine hydrochloride and paraformaldehyde in Examples 5-7 and Comparative Examples 5-6 is the same as the total amount of dopamine hydrochloride and paraformaldehyde in Example 1, and the preparation process and other process parameters of Examples 5-7 and Comparative Examples 5-6 are exactly the same as those in Example 1.
[0081] The catalytic activity of the carbonyl sulfide hydrolysis catalysts prepared in Examples 5-7 and Comparative Examples 5-6 was tested by the same method as in Test 1, wherein the weight ratio of dopamine hydrochloride to paraformaldehyde in Examples 5-7 and Comparative Examples 5-6 and the test results are shown in Table 1.
[0082] Table 1 Test results
[0083]
[0084]
[0085] From the test results in Table 1, it is found that the mass ratio of the raw material dopamine hydrochloride to paraformaldehyde is an important factor affecting the catalytic activity of the carbonyl sulfide hydrolysis catalyst. When the mass ratio of dopamine hydrochloride to paraformaldehyde is too small or too high, the catalytic activity of the prepared catalyst will show a significant downward trend. The framework and structural defects of porous carbon in the entire catalyst preparation process have a direct impact on the manifestation of nitrogen doping ability. Preferably, when the mass ratio of dopamine hydrochloride to paraformaldehyde is 0.5 to 1:1, the prepared carbonyl sulfide hydrolysis catalyst has a higher catalytic activity.
[0086] Comparative Example 7
[0087] Comparative Example 7 adopts the same preparation method as Example 1 to prepare a carbonyl sulfide hydrolysis catalyst, except that the weight ratio of potassium hydroxide to the second material is changed in Comparative Example 7, but the total amount of potassium hydroxide and the second material in Comparative Example 7 is the same as the total amount of potassium hydroxide and the second material in Example 1, and the preparation process and gas process parameters of Comparative Example 7 are exactly the same as those in Example 1.
[0088] Among them, the weight ratio of potassium hydroxide powder to the second material in Comparative Example 7-A group is 0.3:1; the weight ratio of potassium hydroxide powder to the second material in Comparative Example 7-B group is 2:1; the catalytic activity of the carbonyl sulfide hydrolysis catalyst prepared in Comparative Example 7-A group and Comparative Example 7-B group was tested by the same method as Test 1, and the test results are as follows:
[0089] The COS conversion rate of the carbonyl sulfide hydrolysis catalyst prepared in Comparative Example 7-A group increases slowly with the increase of temperature. The study found that the highest COS conversion rate only reached 66.5%.
[0090] The COS conversion rate of the carbonyl sulfide hydrolysis catalyst prepared in Comparative Example 7-B group increases slowly with the increase of temperature. The study found that when the temperature reaches 150°C, the COS conversion rate reaches 100%.
[0091] The study found that the addition ratio of potassium hydroxide powder is a very important key factor affecting the performance of the catalyst product. If the addition ratio is too small or too large, it will affect the porosity and nitrogen doping effect of the catalyst sample, and will also greatly reduce the catalytic activity of the carbonyl sulfide hydrolysis catalyst.
[0092] Comparative Example 8
[0093] Comparative Example 8 uses the same preparation method as Example 1 to prepare a carbonyl sulfide hydrolysis catalyst, except that the temperature of the etching treatment is changed in Comparative Example 8. The preparation process and other process parameters of Comparative Example 8 are exactly the same as those of Example 1.
[0094] Among them, the etching temperature in the comparative example 8-A group is 700°C; the etching temperature in the comparative example 8-B group is 1000°C; the catalytic activity of the carbonyl sulfide hydrolysis catalyst prepared in the comparative example 8-A group and the comparative example 8-B group is tested by the same method as in test 1, and the test results are as follows:
[0095] Comparative Example 8-A: The COS conversion rate of the carbonyl sulfide hydrolysis catalyst prepared in Group A increases slowly with the increase of temperature. The study found that the highest COS conversion rate only reached 55.3%.
[0096] Comparative Example 8-B Group Prepared Carbonyl Sulfide Hydrolysis Catalyst The COS conversion rate of the carbonyl sulfide hydrolysis catalyst increases slowly with the increase of temperature. The study found that the highest COS conversion rate only reached 88.6%.
[0097] The study found that the temperature of the etching treatment is a very important key factor affecting the performance of the catalyst product. If the temperature of the etching treatment is too low or too high, it will affect the porosity and nitrogen doping effect of the catalyst sample, and will also greatly reduce the catalytic activity of the carbonyl sulfide hydrolysis catalyst.
[0098] The invention discloses a method for preparing a carbonyl sulfide hydrolysis catalyst. In the preparation process, a block copolymer, dopamine hydrochloride and polyformaldehyde are used as raw materials, and high-temperature carbonization treatment is directly performed after uniform grinding. Then, the calcined product obtained after carbonization is mixed with potassium hydroxide powder for rapid grinding, and then etching carbonization treatment is performed under nitrogen protection, washing, and drying to obtain the carbonyl sulfide hydrolysis catalyst. The method adopts a solvent-free method to prepare a novel nitrogen-doped porous carbon catalyst. Through the coordinated cooperation of three processes of mechanical grinding, high-temperature calcination and KOH etching treatment, and targeted adjustment of influencing factors such as raw material ratio and process parameters, the prepared carbonyl sulfide hydrolysis catalyst has an ordered mesoporous structure and abundant structural defects, more nitrogen sites, stronger nitrogen doping ability, and exhibits higher catalytic activity when catalytically eliminating carbonyl sulfide. The preparation method is simple to operate and easy to control.
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbonyl sulfide hydrolysis catalyst, characterized in that: The following steps are involved: Step 1, weighing the block copolymer, dopamine hydrochloride and paraformaldehyde, mixing and grinding them evenly to obtain a first material; the weight ratio of the dopamine hydrochloride to the paraformaldehyde is 0.5 to 2:1; Step 2, subjecting the first material obtained in step 1 to high-temperature carbonization treatment under nitrogen conditions to obtain a second material; Step 3, mixing the second material obtained in step 2 with potassium hydroxide powder and grinding them, and then etching the ground material under nitrogen conditions to obtain a third material; wherein the weight ratio of the potassium hydroxide powder to the second material is 0.5-1.5:1; the etching treatment conditions are heating to 800-900 ° C at a heating rate of 1-2 ° C / min and maintaining for 60-120 min; Step 4, neutralizing the third material obtained in step 3 with an acid solution, washing to neutrality, and drying to obtain a carbonyl sulfide hydrolysis catalyst; Wherein, in the step 1, the raw materials are added in amounts by weight: 15 to 25 parts of the block copolymer; 3 to 6 parts of the dopamine hydrochloride; and 3 to 8 parts of the paraformaldehyde.
2. The method for preparing a carbonyl sulfide hydrolysis catalyst according to claim 1, characterized in that: In the step 1, the weight ratio of the dopamine hydrochloride to the paraformaldehyde is 0.5 to 1:
1.
3. The method for preparing a carbonyl sulfide hydrolysis catalyst according to claim 1, characterized in that: In the step 1, the block copolymer is F127 or P123.
4. The method for preparing a carbonyl sulfide hydrolysis catalyst according to claim 1, characterized in that: In step 2, the high temperature carbonization treatment is carried out under the conditions of heating to 700-900°C at a heating rate of 5-10°C / min and maintaining for 30-90 min.
5. The method for preparing a carbonyl sulfide hydrolysis catalyst according to claim 1, characterized in that: In step 3, the weight ratio of the potassium hydroxide powder to the second material is 1.0 to 1.5:
1.
6. The method for preparing a carbonyl sulfide hydrolysis catalyst according to claim 1, characterized in that: In step 4, the acid solution is a sulfuric acid solution or a hydrochloric acid solution with a concentration of 0.2 to 2 mol / L.
7. The method for preparing a carbonyl sulfide hydrolysis catalyst according to claim 1, characterized in that: In step 4, the drying temperature is 60-120° C. and the drying time is 12-48 h.
8. A carbonyl sulfide hydrolysis catalyst prepared by the method for preparing a carbonyl sulfide hydrolysis catalyst according to any one of claims 1 to 7.
Citation Information
Patent Citations
Nitrogen doped ordered mesoporous carbon material, and preparation and application of material
CN108483421A